2017
DOI: 10.1111/jav.01564
|View full text |Cite
|
Sign up to set email alerts
|

Vocal plasticity in mallards: multiple signal changes in noise and the evolution of the Lombard effect in birds

Abstract: Signal plasticity is a building block of complex animal communication systems. A particular form of signal plasticity is the Lombard effect, in which a signaler increases its vocal amplitude in response to an increase in the background noise. The Lombard effect is a basic mechanism for communication in noise that is well-studied in human speech and which has also been reported in other mammals and several bird species. Sometimes, but not always, the Lombard effect is accompanied by additional changes in signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 71 publications
1
1
0
Order By: Relevance
“…Our results also suggest that the call amplitude increases in the presence of anthropogenic noise. Similar results have been shown in the literature for biotic noise, where studies have reported that the Lombard effect is a mechanism widely used by birds to avoid sound masking (Lampe et al, 2010;Zollinger and Brumm, 2011;Dorado-Correa et al, 2018;Singh et al, 2019). Zollinger and Brumm (2015) showed that changes in amplitude can have several costs for birds, for example, affecting sexual selection, defense of territory, condition and energy.…”
Section: Discussionsupporting
confidence: 85%
“…Our results also suggest that the call amplitude increases in the presence of anthropogenic noise. Similar results have been shown in the literature for biotic noise, where studies have reported that the Lombard effect is a mechanism widely used by birds to avoid sound masking (Lampe et al, 2010;Zollinger and Brumm, 2011;Dorado-Correa et al, 2018;Singh et al, 2019). Zollinger and Brumm (2015) showed that changes in amplitude can have several costs for birds, for example, affecting sexual selection, defense of territory, condition and energy.…”
Section: Discussionsupporting
confidence: 85%
“…In humans, the magnitude of the Lombard response has been shown to vary according to experimental design, but increases in vocal amplitude generally range from 0.05 to 0.4 dB per 1 dB increase in noise level (Table 1; Garnier et al, 2010;Hotchkin and Parks, 2013). A similar Lombard response magnitude in the range of 0.2 to 0.8 dB per 1 dB increase in noise level has been demonstrated for other primates (Brumm et al, 2004;Egnor and Hauser, 2006) as well as bats (Tressler and Smotherman, 2009) and several different bird taxa (Brumm and Todt, 2002;Cynx et al, 1998;Dorado-Correa et al, 2018). Thus, many highly vocal terrestrial animals display a Lombard response that helps to partially offset the reduction in active space, yet none of them fully compensate for increased ambient noise and, therefore, face a loss of active space during periods of increased noise.…”
Section: Introductionmentioning
confidence: 60%